Genetic Variability of Oil Palm (Elaeis guineensis Jacq.) Deli Dura Inter-Crosses Population in The MPOB Research Station Hulu Paka, Terengganu, Malaysia - Fadila, Ahmad Malike; Marhalil, Marjuni; Zulkifli, Yaakub; Shamsudin, Noraziyah Abd Aziz; Oyebamiji, Yusuf Opeyemi (Malaysian Applied Biology, 2024)
The oil palm Deli dura breeding population is the most widely used dura for breeding and seed production. Due to its narrow genetic base, with current material originating from the four initial dura palms of Bogor, the Deli dura is presumed to have low genetic diversity. A total of 35 MPOB Deli dura inter-crosses from eight paternal parents were characterized based on 22 different traits including bunch yields, bunch quality components, as well as other vegetative and physiological traits. Based on the principal component analysis of the collected data, the first five components (PC1-PC5) possessing eigenvalues surpassing 1, contributed to 97.83% of the overall variance. PC1, with the highest variation (30.88%), was characterized mainly by vegetative and physiological traits, while PC2, with about 26.02% variation, was primarily associated with bunch quality components. The principal component score plot suggests that populations of the Johor Labis paternal parents 0.278/318 and 0.278/295 are unique populations and can be used in further breeding programmes. Besides, the populations from Ulu Remis (0.280/68) and Ulu Remis × Elmina (0.281/44) paternal parents were positively associated with PC2, suggesting strong performance in bunch quality components. Cluster analysis indicated that all populations were clustered into three main groups comprised of several sub-clusters, with populations of paternal parents 0.279/48 (Banting) and 0.281/74 (Banting) were outliers in the second and third clusters, respectively. In overall, the study revealed the presence of variation among the Deli dura inter-crosses based on the traits evaluated. These results will be useful for the selection of specific populations for genetic improvements of bunch yield, bunch quality, as well as vegetative and physiological characteristics.